CCI on Neural Tissue Induces Mitochondrial Dysregulation in 3D Microglial Tissue - Bakhshi, Rushil. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Biomedical Engineering.; Advisor: David Kaplan.; Committee: David Kaplan, Brian Timko, and Barry Trimmer.; Keyword: Biomedical engineering.